[Cost Evaluation of First-Year Treatment for Locally Advanced or Metastatic Urothelial Carcinoma with Chemotherapy Plus Avelumab vs Chemotherapy Plus Best Supportive Care: A Cost of Care Model] - Roggeri, Daniela Paola; Roggeri, Alessandro; Provenzano, Anna Maria; Boffo, Francesca Ludovica; Iacovelli, Roberto (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
BACKGROUND: Avelumab is indicated as monotherapy for the first-line maintenance treatment of adult patients with locally advanced or metastatic urothelial carcinoma (la/mUC) who are progression free following platinum-based chemotherapy. This study aimed to estimate the direct medical costs of treating patients with la/mUC, from Italian National Health Service (NHS) perspective.METHODS: A model was developed to estimate the healthcare costs for the first year of treatment with platinum-based chemotherapy as induction therapy followed by maintenance with avelumab and best supportive care (BSC) (avelumab + BSC) vs platinum-based chemotherapy as induction therapy followed by best supportive care (BSC). At the end of firstline treatment (including maintenance) or at disease progression, patients may receive subsequent active treatment or BSC. Estimates of patient survival is determined by the published overall survival (OS) of the systemic treatment received in the first-line setting. Costs and tariffs valid as of 2024—including drug acquisition and administration, disease management and adverse event (AE) management—were calculated, including subsequent therapy costs, according to treatment duration, AEs risk, disease monitoring, progression-free survival and OS. Unit costs used are ex-factory prices net of mandatory price reductions for drugs and reimbursement rates, and DRGs for healthcare services and admissions.RESULTS: While the introduction of avelumab as first-line maintenance therapy is associated with an increase in annual drug expenditure in this setting (49,710€), the overall impact on healthcare expenditure is relatively modest (21,241€/year). The avelumab + BSC arm demonstrated significant reductions in costs related to subsequent therapies (−22,385€/year) and disease monitoring and management (−6,287€/year). The impact on drug administration costs was minimal (126€/year), as was the incremental cost related to AEs (77€/year), highlighting avelumab’s favorable tolerability profile.CONCLUSIONS: The estimated increase in direct healthcare costs resulting from the use of avelumab as a first-line maintenance treatment, support its use as SoC in patients who receive 1L platinum-based chemotherapy and are progression free. Understanding the economic burden associated with la/mUC treatments may facilitate informed decisions, their selection and optimal sequencing